2023
DOI: 10.1177/00472875231158598
|View full text |Cite
|
Sign up to set email alerts
|

Power of Sentiment Expressions on Peer-to-Peer Rental Platforms: A Mixed-Method Approach

Abstract: Studies have confirmed the ineffectiveness of sentiment expressions generated by sellers in improving guests’ purchasing intentions. However, how sentiment expressions can influence guest behavior and host performance remains unclear, given the relative importance of seller-generated content in peer-to-peer rental platforms. After collecting data from Airbnb and developing empirical models, this study confirmed that hosts’ sentiment expressions largely benefit from their online performance. This case is especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Further, hosts' sentiment expressions increase the demand for their listings (X. Zhang et al, 2023), and self-presentation signaling social values can enhance hosts' revenues (Garcı´a et al, 2020). Regarding consumers, researchers have identified that consumers are motivated to use P2P accommodation sites due to various factors such as local authenticity, sharing economy ethos, and home benefits (Guttentag et al, 2018).…”
Section: Airbnb and Repurchase Intentionsmentioning
confidence: 99%
“…Further, hosts' sentiment expressions increase the demand for their listings (X. Zhang et al, 2023), and self-presentation signaling social values can enhance hosts' revenues (Garcı´a et al, 2020). Regarding consumers, researchers have identified that consumers are motivated to use P2P accommodation sites due to various factors such as local authenticity, sharing economy ethos, and home benefits (Guttentag et al, 2018).…”
Section: Airbnb and Repurchase Intentionsmentioning
confidence: 99%